Rancang Bangun Photo Kiosk Berbasis Web Dengan Multiple Display - Stephanus Eko Wahyudi (Jurnal Informatika dan Sistem Informasi, 2015)
Taking self portrait is one form of self-expression that is currently favored by people around the world. The development of Internet technologies as well as the technologies provided by gadgets allow the users to take a very good picture quality due to the high quality of the camera. The people need of self expression can be used to attract the crowd in a event organised in public places. Provision of Photo Kiosk facilities - a computer kiosk equipped with a camera, will be able to attract the visitors to try this activity. Results of the photo displayed on the screen in large measure around the location will also increase interest in using the application. This application was developed using web technology with three-tier system, using HTML, CSS, Jquery on the client side, and using PHP and MySQL on the server side. This applications tested in an event at the mall, where applications run well, although the image quality is closely related to the quality of the camera as well as the lighting conditions in the area of the exhibition site.